Is natural science education fully effective? - Paśko, Jan Rajmund; Paśko, Ingrid (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
The introduction outlines how natural science was taught in the past and how it is taught now. Next, the research results are presented with the respondents being university students of Pre-school and Early-school Education degree courses. As part of the study, the respondents had to answer five questions about common natural phenomena. The analysis of the answers gave rise to the conclusion that the examined university students were not able to explain the natural phenomena using the molecular theory of matter; this is due to negative transfer at an early stage of natural science education. Based on the results of the study, it is suggested that natural phenomena and processes should be explained using the molecular theory of matter even at an early stage of primary education.